Regulated Inflammation and Lipid Metabolism in Colon mRNA Expressions of Obese Germfree Mice Responding to Enterobacter cloacae B29 Combined with the High Fat Diet - Yan, Huiying; Fei, Na; Wu, Guojun; Zhang, Chenhong; Zhao, Liping; Zhang, Menghui (Frontiers in Microbiology, 2016)
Increased evidences have demonstrated that gut microbiota targeted diet intervention can alleviate obesity and related metabolic disorders. The underlying mechanism of interactions among diet, microbiota and host still remains unclear. Enterobacter cloacae B29, an endotoxin-producing strain dominated in the gut of a morbidly obese volunteer (weight 174.8 kg, BMI 58.8 kg m-2) was isolated and transplanted to germfree mice (inoculated 1010 cells of B29 per day for one week). Using deep mRNA sequencing technology, we compared different gene expression profiles in the colon samples of the germfree mice treated with/without B29 and/or high fat diet (HFD) for 16 weeks and identified 279 differential expressed genes in total, including up-regulated genes Apoa4 (fold change, 2.77), Ido1 (2.66), Cyp4a10 (7.01), and down-regulated genes Cyp2e1 (0.11), Cyp26b1 (0.34), Akr1b7 (0.42), Adipoq (0.36), Cyp1a1 (0.11), Apoa1 (0.44), Npc1l1 (0.37), Tff2 (0.13), Apoc1 (0.30), Ctla2a (0.34), Mttp (0.49), Lpl (0.48). Fifty-nine GO biological processes and five KEGG pathways, particularly the peroxisome proliferator-activated receptors (PPARs) signaling pathway, were significantly enriched in response to HFD+B29, which were mainly relevant to inflammation and the metabolism of lipid, lipoprotein and sterols. These functional changes were consistent with the developed obesity, insulin-resistance, and aggravated inflammatory conditions of the HFD+B29 mice. This work provides insight into the gene expression changes in response to HFD+B29, helping to understand the mechanism of the interactions among HFD, B29 and the germfree mice.